Recent developments on PET radiotracers for TSPO and their applications in neuroimaging - Zhang, Lingling; Hu, Kuan; Shao, Tuo; Hou, Lu; Zhang, Shaojuan; Ye, Weijian; Josephson, Lee; Meyer, Jeffrey H.; Zhang, Ming-Rong; Vasdev, Neil; Wang, Jinghao; Xu, Hao; et al. (Acta pharmaceutica Sinica. B, 2021)
The 18 kDa translocator protein (TSPO), previously known as the peripheral benzodiazepine receptor, is predominately localized to the outer mitochondrial membrane in steroidogenic cells. Brain TSPO expression is relatively low under physiological conditions, but is upregulated in response to glial cell activation. As the primary index of neuroinflammation, TSPO is implicated in the pathogenesis and progression of numerous neuropsychiatric disorders and neurodegenerative diseases, including Alzheimer's disease (AD), amyotrophic lateral sclerosis (ALS), Parkinson's disease (PD), multiple sclerosis (MS), major depressive disorder (MDD) and obsessive compulsive disorder (OCD). In this context, numerous TSPO-targeted positron emission tomography (PET) tracers have been developed. Among them, several radioligands have advanced to clinical research studies. In this review, we will overview the recent development of TSPO PET tracers, focusing on the radioligand design, radioisotope labeling, pharmacokinetics, and PET imaging evaluation. Additionally, we will consider current limitations, as well as translational potential for future application of TSPO radiopharmaceuticals. This review aims to not only present the challenges in current TSPO PET imaging, but to also provide a new perspective on TSPO targeted PET tracer discovery efforts. Addressing these challenges will facilitate the translation of TSPO in clinical studies of neuroinflammation associated with central nervous system diseases. The 18 kDa translocator protein (TSPO) expression in the central nervous system is upregulated in response to glial cell activation. There is a great potential for the future application of TSPO radioligands as diagnostic and prognostic tools, as well as for assessing therapeutic interventions for neurologic diseases. [Display omitted]